Are autologous stem cell transplants still required to treat myeloma in the era of novel therapies?: a review from the chronic malignancies working party of the EBMT - Garderet, Laurent; Schönland, Stefan (Biology of blood and marrow transplantation, 2020)
Melphalan at a myeloablative dose followed by autologous stem cell transplantation (ASCT) remains the standard of care for transplant-eligible patients with myeloma. However, therapies such as new immunomodulatory drugs and proteasome inhibitors and, more recently, monoclonal antibodies and chimeric antigen receptor T cells are challenging the traditional role of ASCT. Which patients benefit from ASCT? Can its use be delayed until first relapse? The field is moving rapidly as novel agents lead to new patient care strategies. The place of ASCT in this changing landscape will be reviewed and reassessed.
Gesehen am 22.10.2021